Cell-surface expression and immune receptor recognition of HLA-B27 homodimers. - Kollnberger, S; Bird, L; Sun, M; Retiere, C; Braud, V; McMichael, A; Bowness, P (2002)
OBJECTIVE: HLA-B27 is capable of forming in vitro a heavy-chain homodimer structure lacking beta(2)-microglobulin. We undertook this study to ascertain if patients with spondylarthritis express beta(2)-microglobulin-free HLA-B27 heavy chains in the form of homodimers and receptors for HLA-B27 homodimers. METHODS: Expression of HLA-B27 heavy chains by mononuclear cells was analyzed by fluorescence-activated cell sorter staining, Western blotting with the monoclonal antibody HC-10, and 2-dimensional isoelectric focusing. Fluorescence-labeled tetrameric complexes of HLA-B27 heavy-chain homodimers were constructed in which each dimer comprised one His-tagged heavy chain and one biotinylated heavy chain, and were used to stain patient and control mononuclear cells and transfected cell lines. RESULTS: Patients with spondylarthritis expressed cell-surface HLA-B27 homodimers. Populations of synovial and peripheral blood monocytes, and B and T lymphocytes from patients with spondylarthritis, and controls carried receptors for HLA-B27 homodimers. Experiments with transfected cell lines demonstrated that KIR3DL1 and KIR3DL2, and immunoglobulin-like transcript 4 (ILT4), but not ILT2, are receptors for HLA-B27 homodimers. CONCLUSION: Patients with spondylarthritis express both HLA-B27 heavy-chain homodimers and receptors for HLA-B27 homodimers. This may be of significance with regard to disease pathogenesis.